Influence of Headteachers' Transformational Leadership Attributes on Academic Performance: A Case of Private Secondary Schools in Uganda - Sengendo, David; Musinguzi, Benon (East African Journal of Education Studies, 2024)
School demographics have changed in recent decades, and so has the type of leadership needed to successfully lead the rapidly changing schools of this Century. School leadership shapes all other variables such as good curriculum, quality teaching, and academic performance. This study was carried out in selected private secondary schools in Uganda. After the realization that investment in private secondary schools exposed the decline of previously well-performing public schools and contributed to the rise of some private schools. The aim was to establish the influence of transformational leadership on academic performance in private secondary schools among other influencers of school effectiveness. A multi-leadership questionnaire was used to gather information from 276 schools, 425 teachers and Directors of studies in the central region of Uganda because this region has the majority of performing, average and underperforming schools. It also has schools in Urban, Rural and semi-urban and it is considered to be the epicentre of educational institutions in the country. Multiple regression analysis was performed to determine the influence of headteachers’ transformation leadership attributes on academic performance at UCE and UACE in private schools for the year 2017-2019. The findings indicated that the headteachers’ transformational leadership attributes of Idealized influence and Inspirational motivation influence academic performance with standard beta coefficients of 0.154 and -0.140 which suggested that that a unit increase in Idealized influence increases academic performance at UCE by 15.4% in private schools in Uganda while a unit increase in Inspirational motivation decreases academic performance at UCE by 14.0%. At UACE idealised influence and Intellectual stimulation were found to have a significant relationship with UACE performance in private secondary schools in Uganda. The standardized beta coefficients for Idealized influence and Intellectual stimulation were -0.144 and 0.129 respectively suggesting that a unit increase in Idealized influence decreases academic performance at UACE by 14.4% in private secondary schools in Uganda while a unit increase in Intellectual stimulation increases academic performance at UACE by 12.9%. The study concludes that transformational leadership has a significant influence on academic performance in private secondary schools. The study recommends that policymakers and investors in Uganda's Education System should closely monitor the school's alignment with the transformational leadership practices for sustainable academic performance in private secondary schools